IMPLEMENTASI KEBIJAKAN PUBLIK KANTOR PERTANAHAN KABUPATEN PATI ATAS PENGECEKAN SERTIFIKAT TANAH BERBASIS ONLINE - Berliani, Lintang; Antoro, Aji Fajar Suryo (Jurnal Progress Administrasi Publik, 2023)
Public services are activities carried out by state officials, including the National Land Agency. BPN has one of the policies in providing online certificate checking services by the PPAT/Applicant. However, in terms of implementation, there were obstacles, both technical and non-technical. The purpose of this study was to find out and analyze the implementation of public policy at the Pati District Land Office for checking online-based land rights certificates. This research is a normative-empirical research, with a descriptive-analytic nature by conducting library research and interviewing employees who work at the Pati District Land Office. The result of this study is that checking online certificates is guaranteed to be valid according to Ministerial Regulation ATR BPN No. 5 of 2017, either through the BPN website or the "Sentuh Tanahku" application, both carried out by the PPAT/Petitioner. This service is carried out to realize good governance and the general principles of good governance. Technical obstacles, namely websites that have errors or down causing the checking process to be hampered, as well as non-technical obstacles from external PPAT/Applicant parties who make mistakes when uploading documents. Pati District Land Office has made efforts to overcome this by conducting outreach and education on online certificate checking to external parties as well as optimizing the performance of Pati District Land Office employees so that this public service policy runs optimally.   Keywords: Implementation of Public Policy; Land Office; Certificate Checking.